Assessing and Visualizing Pilot Performance in Traffic Patterns: A Composite Score Approach - Quentin Chenot; Florine Riedinger; Frédéric Dehais; Sébastien Scannella (Safety)
Objective measurement of pilot performance has long been a research challenge. This study introduces a new composite score that combines various flight metrics, along with its visual representation through an online application. Thirty general aviation pilots completed flight simulator scenarios under different Flight Rules (VFR: Visual Flight Rules vs. IFR: Instrument Flight Rules) and difficulty levels (Low vs. High). Workload was assessed using subjective and objective indicators. The composite score was developed using flight parameter compliance, approach stability, and landing quality. Workload indicators confirmed the scenario difficulties, showing significant increases under IFR compared to VFR and in High vs. Low difficulty conditions. As predicted by multiple resources theory, the composite score correlated negatively with workload, particularly in IFR conditions, demonstrating its effectiveness in assessing pilot performance. In a follow-up questionnaire, pilots rated the online application positively, highlighting its usefulness in understanding their performance and recognizing its potential for pilot training.